THE HUMAN VARIOME PROJECT COUNTRY NODE OF ARGENTINA IN THE FIRST TWO YEARS OF ACTIVITY: PAST, PRESENT AND FUTURE - Solano A.R.; Garrido M.; Mele P.G.; Podestá E.J.; Reichardt J.K.V. (BAG. Journal of Basic and Applied Genetics, 2019)
The Human Variome Project (HVP) is an international effort aiming systematically to collect and share information on all human genetic variants. It has been working for years in collaboration with local scientific societies by establishing systems to collect every genetic variant reported in a country and to store these variants within a database repository: LOVD (Argentinian chapter: ar.lovd.org). Formally established in 2017 in the Argentinian Node, up to June 2019 we collected more than 25,000 genetic variants deposited by 17 different laboratories. Nowadays the HVP country nodes represent more than 30 countries. In Latin America there are four country nodes: Argentina, Brazil, Mexico and Venezuela; the first two interacted recently launching the LatinGen database. In the present work we want to share our experience in applying the HVP project focusing on its organization, rules and nomenclature to reach the goal of sharing genetic variants and depositing them in the Leiden Open Variation Database. Contributing laboratories are seeking to share variant data to gain access all over the country. It is one of our goals to stimulate the highest quality by organizing courses, applying current nomenclature rules, sponsoring lectures in national congresses, distributing newsletter to serve the Argentinian genomics community and to stimulate the interaction among Latin America countries. Key words: Data sharing, Argentinian chapter of LOVD, Human Variome Project (HVP)-Argentina